Sludge Under Suspicion: Explaining Perceptions of Risks from a Relatively "Unknown" Technology - Lulu Rodriguez; Jane W Peterson (Journal of Applied Communications, 1996)
Factors such as knowledge about the technology and trust in technology-generating institutions influenced people's decisions about the acceptability of applying treated sludge on Iowa's agricultural lands.